-5(x-3)+35=4

Simple and best practice solution for -5(x-3)+35=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(x-3)+35=4 equation:


Simplifying
-5(x + -3) + 35 = 4

Reorder the terms:
-5(-3 + x) + 35 = 4
(-3 * -5 + x * -5) + 35 = 4
(15 + -5x) + 35 = 4

Reorder the terms:
15 + 35 + -5x = 4

Combine like terms: 15 + 35 = 50
50 + -5x = 4

Solving
50 + -5x = 4

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-50' to each side of the equation.
50 + -50 + -5x = 4 + -50

Combine like terms: 50 + -50 = 0
0 + -5x = 4 + -50
-5x = 4 + -50

Combine like terms: 4 + -50 = -46
-5x = -46

Divide each side by '-5'.
x = 9.2

Simplifying
x = 9.2

See similar equations:

| z^2-8z-7= | | -5(x-3)=35+4 | | 5z+9=-2 | | 3d(d+1)-5(d^2-2d+2)= | | x+5+(x+1)=22 | | 2(c-2)=3(2x+6) | | 3+.50x=15 | | 6x^2+28x+49=1936 | | y^2=-x^2+1 | | 2k+34=70-7k | | 3z-1=13 | | 5(2x-2)+2(4x-5)=52 | | a*(5)=a*14406+(5-1)*-4816 | | 12x^2-80x+91=0 | | 14=5+u | | 0=a^2-100 | | 6(m-5)=4m+4 | | 6.5+2.5x=11 | | -9-(-4)=3 | | h=-16t^2+64t+190 | | 4a+1=3 | | 6x+(5x-7)+(2f^2+2)+x=5x^2+19x+11 | | -24x+18=-24x-18 | | 36=121x^2 | | 4y^2+37y+40=0 | | -42=14406+(4-1)d | | 2(5x-2y+1)-2(3y+2x)= | | 4y^2-31y-45=0 | | 6(2n-4)=(8n-2)-1 | | 8a+6*9a+10=304 | | 4x-26=3x+13 | | a*5=a*14406+(5-1)*-3600.25 |

Equations solver categories